2023
DOI: 10.3389/fpsyt.2022.989492
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation mediated the effect of dietary fiber on depressive symptoms

Abstract: Background and aimsPrevious studies showed that inflammation affects depressive symptoms. Dietary fiber may be associated with inflammation and depressive symptoms. We aimed to investigate the relationship between inflammation and depressive symptoms at different levels of dietary fiber intake and to explore whether dietary fiber affects depression through inflammation.MethodsA total of 8,430 National Health and Nutrition Examination Survey (NHANES) samples were collected between 2015 and 2018. Factor analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…The visualizations completed for the top four continuous covariates were concordant with current literature: there is strong epidemiological evidence that good diet is associated with decreased risk of depression 22 . Many authors have noted statistically significant associations between Vitamin B6, Dietary Fiber, Potassium Intake, Vitamin E, Low Fat and Low Cholesterol Diet, Copper, Caffeine, Lutein Zeaxanthin, Phosphorous, Food Folate, Folate, Vitamin K, Iron, Theobromine, Total Choline, Magnesium, Sodium, Grams of Protein, Vitamin B12, Fiber, and Zinc similarly to our study 38–43 . Since visualizations for risk factors match literature relationships, we have increased confidence that the machine learning model is able to capture the actual physiological relationships of these covariates 44–51 .…”
Section: Discussionsupporting
confidence: 80%
“…The visualizations completed for the top four continuous covariates were concordant with current literature: there is strong epidemiological evidence that good diet is associated with decreased risk of depression 22 . Many authors have noted statistically significant associations between Vitamin B6, Dietary Fiber, Potassium Intake, Vitamin E, Low Fat and Low Cholesterol Diet, Copper, Caffeine, Lutein Zeaxanthin, Phosphorous, Food Folate, Folate, Vitamin K, Iron, Theobromine, Total Choline, Magnesium, Sodium, Grams of Protein, Vitamin B12, Fiber, and Zinc similarly to our study 38–43 . Since visualizations for risk factors match literature relationships, we have increased confidence that the machine learning model is able to capture the actual physiological relationships of these covariates 44–51 .…”
Section: Discussionsupporting
confidence: 80%
“…The components and quality of the diet can also impact the inflammatory state. Research has shown that diets with higher scores on the Dietary Inflammatory Index (DII) are associated with a greater likelihood of depression occurrence ( 28 ). There are also reports indicating that the Systemic Inflammation Index (SII) might contribute to the development of depression ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consuming a fiber-rich diet promotes the growth of gut bacteria that produce butyrate [ 47 , 48 , 49 ], consequently lowering stress levels and depression [ 50 ]. Zhang et al’s 2023 study observed that in individuals with high dietary fiber intake, there was no association between symptoms of depression and dietary inflammatory index (DII), a sociodemographic characteristic representing dietary inflammation and C-reactive protein (CRP) [ 51 ]. A previous study by Caspani et al, 2019 explored the mechanism used by the gut microbiota in modulating metabolites that influenced mood changes in major depressive disorder (MDD) through actions in the gut–brain axis [ 52 ].…”
Section: The Psychological Toll Of Food Insecuritymentioning
confidence: 99%